Processing and evaluation of an investment cast magnesium-base alloys - Idris, Mohd. Hasbullah (2001)
The research reported in this thesis was conducted in two phases. The first phase considered the suppression of mould-metal reaction. The approaches were to: cast the alloy with four pouring and mould preheat temperature combinations i.e. 680°C and 780°C pouring temperatures, and 300°C and 600°C mould preheat temperatures in five different mould refractory materials. CaF2 was then used as an inhibitor with the most suitable of the five refractory materials and the moulds were cast with the best pouringlmould preheat temperature combination.The results showed that the best casting was produced by pouring the alloy at the temperature combination of 680°C and 300°C pouring and mould preheat temperature respectively in a zirconia refractory mould without an inhibitor. Incorporating CaF2 inhibitor in the mould at levels of 20 wt% and 5 wt% of the zirconia poured at 680°C and 300°C, pouring and mould preheat temperatures respectively, produced a casting with a relatively bright metallic appearance. Further experimentation on the addition of 20 wt% of CaF2 in a zirconia mould poured in the temperature range between 680°C and 780°C and with a 300°C mould preheat temperature revealed that the mould-metal reaction occurred above the pouring temperature of 740°C. The second phase concentrated on establishing the procedure for grain refinement and considered mould inoculation and vibration methods to grain refine the alloy. The effect of two melt conditions, i.e. zirconium-treated and zirconium-free melts, was investigated for four moulds, which had mould face coats containing 0%, 0.5%, 5% and 10% zirconium. The melts were poured at a temperature of 740°C in moulds preheated to 300°C. The investigation using vibration was conducted for two melt conditions, namely zirconiunl-treated and zirconium- free melts. Four mould vibration conditions were considered: no vibration, and vibration at frequencies of 5, 9 and 13 Hz. The results showed that none of the in-mould additions exhibited any effect on grain refinement for either of the melts. The investigation on the effect of vibration showed that the grain size decreased as the frequency was increased for both the zirconium-treated and zirconium-free melts. Mechanical properties were determined for samples produced using three casting conditions: zirconium-treated melt vibrated at a frequency of 13 Hz; zirconium-treated melt without vibration and a zirconium-free melt without vibration. The results showed that the highest yield strength and hardness were 69.3 1 MPa and 63.86 Hv respectively. These were obtained from the tensile test sample produced from the melt treated with zirconium and vibrated at the frequency of 13 Hz. Correspondingly, the grain size was found to be the smallest with a grain size of 56.9 pm when compared to the other castings